The Pompeii Column: The Lost Monument of Istanbul - Kaya Ateş, Elif; Yılmaz, Nazende (Journal of History Culture and Art Research, 2024)
This study analyzes information from German travel books to unveil the Pompeii Column, constructed in the Byzantine capital but reportedly torn down at the end of the 17th century. The written descriptions of the travelers and the engravings and maps drawn by the artists accompanying them provide comprehensive details about the ruined works. Firstly, the location of Öreke Rocks near Rumeli Feneri, the site of the Pompeii Column, is examined in terms of mythology and the legends surrounding it. The details of the votive altar and the column are presented in this context. Travel books authored by German-speaking travelers who saw the structure's appearance during their visit to Istanbul in the 16th and 17th centuries were studied in-depth for a thorough examination. Through these accounts, it seeks to gather novel data on the Pompeii Column, which has not survived to the present day and has not received thorough study yet. Travelers made this trip despite the challenging conditions because they wanted to see and study the Pompeii Column and maybe even have their names etched on it. Upon compiling the data from German travel books, it becomes evident that the Pompei Column is a Byzantine-era signal column and an ancient altar as a base situated on the largest of the rocks known as Öreke Rocks, a short distance from Rumeli Feneri. The single piece of White marble column is composed of three distinct components stacked on top of one another. The top of the column is shaped like a wreath, while the middle section and base are diverse from the upper piece.